Factors influencing request of light steel in town of Pekanbaru - Arif Lesmana; Azwar Harahap; Eka Armas Pailis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This Research is conducted in Town of Pekanbaru in June Year 2013 - October Year months 2013. As for intention of this research is to know factors influencing request of light steel in Town of Pekanbaru.This file is used in research data of secondary and primary data and with method of analisisis data is quantitative descriptive analysis. As for becoming population in this research is consumer of light steel in Town of Pekanbaru, where amount of sampel the taken is counted 94 responder by using formula of Slovin.From result of research known that factors influencing request of light steel is light steel price, friendliness to light steel and environment hold up to white ants. Become to be expected to light steel distributor in Town of Pekanbaru more majoring the of the factors so that satisfied consumer use light steel which with quality but its price is reached.Keyword: Request, light steel, price, friendly of environment, and hold up to white ants.